THE NATURE OF ULTRAMAFIC XENOLITHS IN THE BASALTS OF LANZAROTE ISLAND (CANARY ARCHIPELAGO) - V. A. Krylova; I. F. Gertner; G. Gutiérrez-Alonso (Геодинамика и тектонофизика)
Mineralogical and geochemical study was performed on peridotite xenolith hosted by amygdaline basalts of Lanzarote Island (Canary archipelago). Their modal composition corresponds to harzburgite. Remarkably, the petrographic composition of the rocks is marked by presence of plagioclase. The isochron shows the age of 267±35 Ma, which might be the initial stage of opening a fragment of the Atlantic Ocean. The peridotites were apparently derived in the magmatic chamber formed by "underplating" triggered by interaction of mantle substrate with the lower crust material.